Immunoelectron microscopy and biochemical studies using three anti-tau antibodies in human brains: associations between pTau and ribosomes - Douglas Price; Jillian Cramer; Colin B. Rogers; Paresh Prajapati; Yamaan Shakhashiro; Peter T. Nelson; Wang-Xia Wang (Acta Neuropathologica Communications)
Abstract The hallmark neuropathological lesions of Alzheimer’s disease (AD) are extracellular amyloid-beta (Aβ) plaque deposits and intracellular Tau neurofibrillary tangles (NFTs). Identifying the intracellular localization of early pathologic changes can enhance our understanding of disease mechanisms and stimulate new approaches in diagnosis and treatment. Despite extensive biochemical studies of AD-related protein aggregates, there have been relatively few studies recently in terms of transmission electron microscopy of proteinaceous lesions in human brains across a range of disease severity. Here we performed immunoelectron microscope studies used three anti-Tau antibodies (MC-1, AT8, and PHF-1) on short post-mortem interval (PMI) human brain tissues obtained from the University of Kentucky Alzheimer’s Disease Research Center (UK-ADRC) autopsy cohort, along with corresponding biochemical and immunofluorescent studies. Although these three antibodies have been reported to label different phases of NFT formation, in our hands they all tended to stain pathologic structures along a continuum that included pretangles and mature NFTs. Immunoelectron microscopy studies, augmented by serial sectioning, revealed that all three Tau antibodies recognize both granular and fibrillary structures in pretangles and early-stage NFTs. Phosphorylated Tau (pTau) immunoreactivity often exhibited a peri-nuclear distribution. The pTau was frequently found localized to ribosomes, either free within the cytoplasm or attached to the endoplasmic reticulum (ER). This observation aligns with previous descriptions, but the enhanced ultrastructural preservation provided improved resolution. Subcellular fractionation and Western blot analyses confirmed the enrichment of pTau in the ER fractions in AD brains. Interestingly, total Tau (including non-phosphorylated Tau) did not preferentially co-purify with the ER in non-AD brains. Immunofluorescent staining revealed that pTau immunoreactivity evolved from cytoplasmic granules in pretangles, with an intracytoplasmic distribution that overlapped complementarily with ribosome and ER markers. Our results suggest that biochemical associations between pTau with ribosomes and ER are a common phenomenon in human aged brains.